MASCULINO DE 46 AÑOS CON TUBERCULOSIS INTESTINAL - Salas Jiménez, Edwin (2012)
We present the case of a 46 years-old male, previously healthy, active  smoker and drug user.Attended at our hospital. He complained of weight loss, malaise, cough and abdominal pain. The Ziehl-Neelsen was positive in sputum, HIV was negative and had a nutritional coefficient of10. During the hospital admission, he presented acute obstructive abdomen and an emergency laparotomy should be performed, with terminal ileon resection and right  hemi colectomy. The histologic analysis showed trans mural granulomatous colitis and the PCR was positive for M. tuberculosis.